Changes in hemodynamic parameters affected by interval hypoxic exercises during the precontest training stage of qualified climbers - Мулик, Вячеслав; Кійко, Андрій (Slobozhanskyi Herald of Science and Sport, 2017)
Viacheslav Mulyk & Andriy Kiyko Purpose: to study the effects of the use of interval hypoxic training (IHT) in the 15–15 mode with breathing through the system into a confined space with a regulated composition of inhaled air in the integrated training process of climbers of the level of preparation of SP-I. Material & Methods: a study was conducted with the participation of the control and experimental groups using medical-biological methods and IHT in the experimental group with using mathematical statistics methods. Results: conducted studies have allowed to determine that the use of the regime of discontinuous hypoxia 15–15 in the training process of the precompetitive period contribute to an increase in the parameters of hemodynamics that affect the adaptation to the action of the load under conditions of hypoxia. Conclusion: reliable changes that are determined during the research testify to the effectiveness of the use of interval hypoxic training 15–15 in the precompetitive training of qualified climbers.